2021
DOI: 10.1002/jgc4.1396
|View full text |Cite
|
Sign up to set email alerts
|

Helping young children understand inherited cancer predisposition syndromes using bibliotherapy

Abstract: Communication with children about hereditary conditions in the family can be difficult for parents. Yet, good communication strategies are leading determinants of adaptation and resilience. With inherited cancer predisposition syndromes that can affect young children such as Li‐Fraumeni syndrome (LFS) and hereditary pheochromocytoma and paraganglioma syndrome (HPPS), genetic testing and subsequent surveillance in at‐risk children is the optimal intervention. Given testing often commences early, providing child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…In agreement with our procedure, it has been recently reported that bibliotherapy using stories, such as our booklet intended for children, helping children understand inherited cancer predisposition syndromes, was useful for children aged 5-10 years old at risk of either Li-Fraumeni syndrome or hereditary PHEO and paraganglioma syndrome, by improving the process of communication between parents and children 16 .…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with our procedure, it has been recently reported that bibliotherapy using stories, such as our booklet intended for children, helping children understand inherited cancer predisposition syndromes, was useful for children aged 5-10 years old at risk of either Li-Fraumeni syndrome or hereditary PHEO and paraganglioma syndrome, by improving the process of communication between parents and children 16 .…”
Section: Discussionsupporting
confidence: 79%
“…The research results of Sidiropoulou & Kountouras (2022) show that bibliotherapy is used to increase one's understanding. Research by Schlub et al (2021) also shows the effectiveness of bibliotherapy as an intervention to provide understanding to someone. Based on the studies above, it can be concluded that bibliotherapy can be used to provide understanding to someone by providing appropriate readings.…”
Section: Introductionmentioning
confidence: 99%
“…As an interactive therapeutic intervention, bibliotherapy uses storytelling as a means to enhance self‐understanding and promote coping skills for children 3–5 . Storybooks have potential to share information about a diagnosis or a treatment plan or a life adjustment associated with illness to expand the child's knowledge 6,7 . Storybooks can also be used to help children understand and deal with relevant emotions, including impending death 8 .…”
Section: Introductionmentioning
confidence: 99%